A METHOD FOR STATOR RESISTANCE MEASUREMENT SUITABLE FOR VECTOR CONTROL - AKIN, E; ERTAN, HB; UCTUG, MY (Ieee, 1994)
[Abstract Not Available]
20th International Conference on Industrial Electronics Control and Instrumentation -- SEP 05-09, 1994 -- BOLOGNA, ITALY